Тарас Шевченко і народна культура - Чава, Катерина Романівна (My University, 2014)
Оцінено роль творчості Т. Шевченка серед народної культури; близькість поета до народних інтересів; аналіз поглядів поета на реальні ситуації,які спіткали народ за його життя. Reviewed creativity Shevchenko role of popular culture; poet proximity to people's interests; analysis of the views of the poet to real situations that have befallen the people in his life.
Keywords: письменник; культура; Тарас Шевченко; writer; culture; Taras Shevchenko